Testing of the Ti foil with TiN coating as an exit window of a pulsed electron accelerator; Vacuum; Vol. 199 - Egorov I. S. Ivan Sergeevich; Smolyanskiy (Smolyansky, Smolyanskii) E. A. Egor Aleksandrovich; Poloskov A. V. Artem Viktorovich; Serebrennikov M. A. Maksim Anatolevich (2022, 2022)
Title screen